Preserving and Presenting the Rotterdam Erasmus Collection since 1868 - Steen, Sanne (Erasmus studies, 2024)
The unique collection of Erasmiana in the Rotterdam Public Library has a long history in which there has been varying attention to acquisition, preservation and presentation. This article describes how individuals such as donors, directors and curators developed the collection since it was first mentioned in 1868. This development is reconstructed through archival sources such as year reports, newspaper articles and material evidence in the collection itself. From this reconstruction, it is possible to distinguish three phases in the history of the Erasmus Collection in which it was treated as respectively an archival collection, a scholarly source and a heritage collection. The case study shows why it is important for scholars who make use of a collection to understand the historical development of its contents and the status of the collection as such. Furthermore, knowledge of the history of a collection is valuable for exploring today’s balance between preservation and presentation.